Growth responses of Clarias gariepinus fingerlings fed differently boiled periods of rubber (Hevea brasilensis) leaves-based diets. Issue 1 (2nd January 2019) - Satimehin, F.P.D; Tiamiyu, L.O.
ABSTRACT: Fingerlings of Clarias gariepinus were fed diets containing 0-min, 5-min, 10-min, 15-min and 20-min inclusion periods of different hydrothermally processed rubber leaves-based diets. After 8 weeks of feeding trials in outdoor hapas, it was observed that growth performance indices such as Mean Weight Gain, Feed Conversion Ratio, Feed Conversion Efficiency, Specific Growth Rate, Protein Efficiency Ratio and Apparent Net Protein Utilization were significantly affected (P < 0.05) across the treatment, where Diet3 (10-min inclusion of hydrothermal processed rubber leaves meal) gave the best result in all the growth performance indices. Inclusion periods of 10 min of boiled rubber leaves meal (RLM) should not be exceeded in the diet of Clarias gariepinus . This limit had no negative effect on growth and also reduces production cost of fish since the leaves are easily available in regions where this plant is cultivated.